Implementation of The Accountability Accounting System as a Tool For Cost Control Effectiveness in Public Companies in The Tirta Manuntung Balikpapan Area - Saputri, Della; Lahaya, Ibnu Abni (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
The company has the goal of providing services to the community and also earning profits for the smooth operation of the company. To realize these goals, the company needs to carry out cost control, cost control, and accountability reporting from the bottom to the top of the unit. The implementation of accountability accounting can help managers in making decisions in the future. This study aims to test the implementation of accountability accounting mechanisms for the effectiveness of cost control in the Tirta Manuntung Balikpapan Regional Public Company. This study uses a comparative casual method with a quantitative approach. Data collection techniques with questionnaires. The sample selection was carried out on the basis of the variables used, namely 5 variables × 10, 50 respondents were obtained in this study. This study used multiple linear regression analysis and the data obtained was analyzed using IBM SPSS statistics 25 software. The results of this study show that all variables, namely organizational structure, planning and budget, implementation and reporting system have a positive and significant effect on cost control